La imputación concreta en los delitos de negociación incompatible y cohecho en las sentencias emitidas por las salas penales de la provincia de trujillo, en el periodo 2011-2015 - Reyes Ríos, Leslie Andrea (2017)
This thesis entitled: "THE IMPUTATION CONCRETE IN THE CRIMES OF NEGOTIATION INCOMPATIBLE AND COHECHO IN THE SENTENCES ISSUED BY THE CRIMINAL ROOMS OF THE PROVINCE OF TRUJILLO IN THE PERIOD 2011-2015"; Addresses the problem regarding the deficiencies in the concrete attribution in the crimes of Incompatible Negotiation and Bribery that have been warned in the sentences issued by the Criminal Chambers of the Province of Trujillo in the period 2011-2015; With the general objective of determining whether or not the principle of specific imputation has been protected. In order to formulate and contrast our hypothesis, in the sense that the principle of concrete imputation in the sentences for Incompatible Negotiation and Bribery issued by the Criminal Chambers of the Province of Trujillo in the period 2011-2015 focusing on the responsibility Of the accused. It has worked on the Theoretical Framework, the first chapter: THE IMPUTATION CONCRETE IN THE CRIMINAL PROCESS, in which it has developed topics such as imputation, legislative antecedents, concrete imputation, its foundation and structure, concrete imputation in the stages of Criminal procedure , The concrete imputation according to the Judgments of the Constitutional Court; As the second chapter has developed: THE GUARANTEES OF THE IMPUTATION IN THE FRAMEWORK OF A DEMOCRATIC STATE OF LAW, in which the following topics have been developed: Guaranteed Criminal Procedure, due process, principle of legality, presumption of innocence, right of Defense and Due justification of judicial decisions; And the third chapter: CRIMES OF CORRUPTION OF OFFICIALS has developed: Incompatible Negotiation Offense and bribery offense. For the development of the present investigation, the inductive-inductive, synthetic analytical, legal and exegetical hermeneutic method was used, where the analysis of normative and doctrinal aspects of the principle of concrete imputation will be carried out; And to determine whether the content of the imputation has been carried out by the tax authorities. The present investigation concludes that the principle of concrete imputation has not been protected in the sentences Incompatible Negotiation and Bribery in the year 2011-2015; So it has also been concluded that the lawyers have questioned some objective elements as a manifestation of the concrete imputation, the same ones that have been decisive in the procedural activity. Finally, it has been concluded that the deficiencies in the concrete imputation that were noticed from the analysis of the sentences of Incompatible Negotiation and Bribes issued by the Criminal Chambers of the Province of Trujillo in the period 2011-2015, has influenced in the Criminal liability of the accused; Inasmuch as it has been convicted in the first instance and acquitted in the second instance by noting violation of this principle